2018
DOI: 10.1186/s40623-018-0859-8
|View full text |Cite
|
Sign up to set email alerts
|

The Qujing incoherent scatter radar: system description and preliminary measurements

Abstract: The Qujing incoherent scatter radar (QJISR), the first one in China with the geographic location (25.6°N, 103.8°E), was brought into operation since the spring of 2014. The QJISR was a mono-static pulsed radar working in the operating frequency 500 MHz, the peak power 2 Megawatt, and a 29-m steerable parabolic dish. This paper mainly presents the basic configuration and implementation of QJISR, including the antenna, transmitter, receiver, signal processing, and data analysis. Some preliminary observation resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…Since from 29 May 2015, the incoherent scatter radar (ISR) at Qujing (103.8°E, 25.6°N) conducted a four consecutive days observation. As introduced by Ding et al (), the Qujing ISR is a pulse‐modulated radar working at the frequency of 500 MHz and maximum peak power of 2 MW. The Qujing ISR system configuration and its data analysis have been described by Ding et al ().…”
Section: Datamentioning
confidence: 99%
“…Since from 29 May 2015, the incoherent scatter radar (ISR) at Qujing (103.8°E, 25.6°N) conducted a four consecutive days observation. As introduced by Ding et al (), the Qujing ISR is a pulse‐modulated radar working at the frequency of 500 MHz and maximum peak power of 2 MW. The Qujing ISR system configuration and its data analysis have been described by Ding et al ().…”
Section: Datamentioning
confidence: 99%
“…The behaviors of NmF 2 and hmF 2 in Liu et al () and Jiang et al () are different from the general view that electron density should decay faster if the ionosphere is at a lower altitude when no external ionization is involved. Further, in a paper which provide a general description of a new‐built incoherent scatter radar (ISR) at Qujing (103.8°E, 25.6°N) of China, Ding et al () reported that the Qujing ISR frequently observed enhancements in electron density in the ionospheric F region during the afternoon‐evening period. Figure 12 of Ding et al (), for example, revealed exactly the same feature that NmF 2 enhances when hmF 2 descends to lower altitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in a paper which provide a general description of a new‐built incoherent scatter radar (ISR) at Qujing (103.8°E, 25.6°N) of China, Ding et al () reported that the Qujing ISR frequently observed enhancements in electron density in the ionospheric F region during the afternoon‐evening period. Figure 12 of Ding et al (), for example, revealed exactly the same feature that NmF 2 enhances when hmF 2 descends to lower altitudes. Thus, it is still an unsolved question on the relationship between the variations of NmF 2 and hmF 2; namely, whether the increase in NmF 2 can be related in general to a drop in hmF 2 or not.…”
Section: Introductionmentioning
confidence: 99%
“…Ding ZH et al (2018b) presented some examples of the Qujing incoherent scatter radar (QJISR). The spectrum shape changes from a single hump to double humps with increasing altitude.…”
Section: Ionospheric Structures and Climatologymentioning
confidence: 99%